CURRENT STATE OF STOCK FOR TANNER CRAB CHIONOECETES BAIRDI RATHBUN, 1924 (CRUSTACEA, DECAPODA) AT THE SOUTH-EASTERN COAST OF KAMCHATKA - O. G. Mikhailova (Известия ТИНРО)
Tanner crab Chionoecetes bairdi is the highly valuable object of commercial fishery dwelling in the seas surrounding Kamchatka Peninsula. Its landings started at the southeastern coast of Kamchatka in early 1980s and continued till 2009, when the fishery was stopped by reasons independent on the stock state. It was launched again in 2017. Now the species is landed mostly in the Petropavlovskaya fishery subzone (62 % of the total allowable catch of tanner crab in Russia in 2019), whereas its stocks at southwestern Kamchatka and in the northwestern Bering Sea are rather low. Modern condition of the tanner crab population and its distribution at southeastern Kamchatka are considered on the data of the trap surveys conducted in spring and summer of 2012 and 2018. Between these years, commercial males of these species spread wider at southeastern Kamchatka and formed commercial aggregations in the northern Avachinsky Bay and in the southern and central parts of the Kronotsky Bay, but were rare southward from Cape Povorotny. They became larger: while size of the males varied in the range 50–170 mm in both years, the males with the carapace width < 120 mm prevailed in 2012, but the large-sized males with commercial size were more numerous in 2018. Percentage of the females in the catches was low both in 2012 and 2018 that is typical for the trap catches. The crabs at the 3rd stage of molting dominated both in May and August of 2012 and 2018. Injury level of the commercial males was rather high and increased from 2012 to 2018 in 8 %. Good current condition of the tanner crab population at southeastern Kamchatka is concluded.